Can taxation predict US top-wealth share dynamics? - Gregor Böhl; Thomas Fischer (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2017)
The level of capital tax gains has high explanatory power regarding the question of what drives economic inequality. On this basis, the authors develop a simple, yet micro-founded portfolio selection model to explain the dynamics of wealth inequality given empirical tax series in the US. The results emphasize that the level and the transition of speed of wealth inequality depend crucially on the degree of capital taxation. The projections predict that - continuing on the present path of capital taxation in the US - the gap between rich and poor is expected to shrink whereas "massive" tax cuts will further increase the degree of wealth concentration.
urn:nbn:de:hebis:30:3-475924
Keywords: D31; H23; G11; 330; wealth inequality; US top-wealth shares; capital taxation; Fokker-Planck equation; Kalman Filter